(untitled) (Huellas, 2022)
Over the last decade, different types of resistance have emerged in urban areas that question the dominant agri-food model and seek to promote and articulate alternative experiences of food production/consumption through different means. Among them, the so-called solidary retailers that distribute food and other products of the basic basket in cities, calling for critical and responsible consumption, are gaining increasing visibility. Within this framework and adopting a case study approach to solidary retailers in the Ciudad Autonoma de Buenos Aires, I propose to analyze the places and discourses that they build/articulate, as an important element to concretize, disseminate and consolidate intermediation. This analysis allowed me to identify virtual places (websites, social networks, WhatsApp groups) and geographical discourses (ideas and geographical metaphors to promote their work and the products they sell) as two main aspects for the reproduction and expansion of these experiences. Research relied on secondary data sources that include: bibliography on each case, retailer’s web pages and social networking sites, journalistic articles and assessments by the actors involved.